Are we really decreasing maternal mortality rate or we are just pushing mothers to late maternal deaths? - Arora, Aashima; Jain, Vanita; Sikka, Pooja; Singh, Aruna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Maternal mortality remains a global concern, and India has made substantial strides in reducing maternal mortality rates (MMR) by about 70%, from 398 /lakh live births in 1997-98 to 99 /lakh live births in 2020. However, it is recognized that maternal mortality represents only tip of iceberg. For every woman who dies, many more survive with severe morbidities, and their long-term outcomes often go unrecorded. Therefore, to truly evaluate maternal health services, it is essential to analyze the long-term outcomes of women discharged with morbidities resulting from complications of pregnancy and childbirth, known as maternal near-miss cases.